2017
DOI: 10.2967/jnumed.116.186353
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of SUV in Oncologic 18F-FDG PET

Abstract: Learning Objectives: On successful completion of this activity, participants should be able to (1) describe the way test-retest studies have been used to measure SUV repeatability, (2) summarize the different methodologic approaches and complexities when analyzing SUV test-retest data, and (3) understand the implications of SUV repeatability for the quantitative assessment of tumor response to treatment.Financial Disclosure: This work was partially funded by grants from the National Institutes of Health (HHSN2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
145
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(154 citation statements)
references
References 38 publications
8
145
1
Order By: Relevance
“…Therefore, the primary analysis emphasizes Bland-Altman limits of agreement (centered around average difference) rather than the RC (centered around zero). For testing group differences, jDj was selected as the primary endpoint to facilitate interpretation as absolute percentage difference (11). Linear mixed-effects regression models were fitted to measure associations between test-retest difference (jDj) and scanning group, patient-level, and lesion-level characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the primary analysis emphasizes Bland-Altman limits of agreement (centered around average difference) rather than the RC (centered around zero). For testing group differences, jDj was selected as the primary endpoint to facilitate interpretation as absolute percentage difference (11). Linear mixed-effects regression models were fitted to measure associations between test-retest difference (jDj) and scanning group, patient-level, and lesion-level characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Scanner qualification (4) and standardization of patient preparation and imaging protocols (5,6) may reduce measurement error. Consistency in scanner protocol parameters such as uptake time, image reconstruction, and scanner maintenance may limit machine error to less than 10% (7-9), but inconsistent or nonoptimized protocols can add error ranging from 18% to more than 40% (7,10,11). In addition, deviations from standards are common even under the scrutiny of a test-retest study (12)(13)(14).…”
mentioning
confidence: 99%
“…In any case, the impact of such a framework on test-retest repeatability of PET measures [101] remains to be carefully assessed.…”
Section: Pif Estimationmentioning
confidence: 99%
“…In a pilot study, 68 Ga-ABY-025 PET uptake quantification suggested a preliminary SUV threshold of 6 for the discrimination of HER2-positive from HER2negative lesions [11,12]. SUV is a highly repeatable measurement; however, it relies heavily on the acquisition and reconstruction protocols used [13].…”
Section: Introductionmentioning
confidence: 99%